A revision of the Carebara pygmaea (Emery, 1887) species group (Hymenoptera: Formicidae) in Thailand - Wimolsuthikul, Chaipat; Yamane, Seiki; Samung, Yudthana; Jaitrong, Weeyawat (Zootaxa, 2024)
The Carebara pygmaea (Emery, 1887) species group in Thailand is reviewed. Among them, five species are recognized, including two newly described species, Carebara adisaki Wimolsuthikul & Jaitrong, sp. nov., and Carebara parvar Wimolsuthikul & Jaitrong, sp. nov., both of which are illustrated based on major and minor workers. In addition, Carebara bokorensis Matsuura & Hosoishi, 2024 is reported in Thailand for the first time. The study also describes a dealate queen of C. pygmaea and an ergatoid queen of C. bokorensis for the first time. Keys to the Thai species of the C. pygmaea species group are provided based on the major and minor workers.